MODEL SIMULASI NUMERIK HUBUNGAN PANJANG BOBOT IKAN TONGKOL (Auxis thazard) PADA PANGKALAN PENDARATAN IKAN LABUAN BAJO KABUPATEN DONGGALA - A. Masyahoro (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
A research on numerical simulation of the relationship between Auxis thazard body length and weight was conducted to study the growth pattern of the fish. The research was done through survey which was initiated by measuring the body length of n fish samples drawn from N fish population. The size of fish population (N) was determined based on the total number of fish collected from any landing catch. The number of fish samples required was based on their variability in the catch yield for each catching period. Data collected was analyzed on the basis of functional relationship between fish fork length (FL) and body weight (W) following the non linear mathematical equation: W (i)  =  qFL(i)b. A numerical simulation was then performed using the techniques of data interpolation and extrapolation. The regression value for the relationship of the two parameters was 3.63 indicating that the growth of the Auxis thazard on the first day of data collection was positive allometric while on the second day it was negative allometric with a regression coefficient of 2.92.